2021
DOI: 10.1021/acsapm.1c00832
|View full text |Cite
|
Sign up to set email alerts
|

Super Tough Polylactic Acid Plasticized with Epoxidized Soybean Oil Methyl Ester for Flexible Food Packaging

Abstract: Polylactic acid (PLA) is a key biopolymer with potential uses in numerous sectors, since it is biocompatible and both biobased and biodegradable. However, brittleness limits its industrial applications where plastic deformation at high impact rates or high elongation is required, for instance, flexible food packaging. In order to overcome this drawback and potentially expand the PLA market, we developed flexible PLA materials plasticized with renewable and biodegradable epoxidized soybean oil methyl ester reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 52 publications
10
56
0
Order By: Relevance
“…Another drawback with PLA food packaging is that it produces a loud noise that consumers perceive as an undesirable property [117]. Zych et al [118] found that plasticization of PLA with epoxidized soybean oil methyl ester achieved an increase in elongation at a break of nearly 800 percent. Furthermore, these films recorded significantly less noise compared to the packaging material of pure PLA.…”
Section: Polylactic Acid (Pla)mentioning
confidence: 99%
“…Another drawback with PLA food packaging is that it produces a loud noise that consumers perceive as an undesirable property [117]. Zych et al [118] found that plasticization of PLA with epoxidized soybean oil methyl ester achieved an increase in elongation at a break of nearly 800 percent. Furthermore, these films recorded significantly less noise compared to the packaging material of pure PLA.…”
Section: Polylactic Acid (Pla)mentioning
confidence: 99%
“…Prior to the analysis, 10 mg of each sample was added to 1 mL of deuterated solvent system CD 2 Cl 2 /TFA-d (1:1, v/v) and placed in an ultrasonic bath set at 30 °C for 4 h. The spectra were acquired using a Bruker Avance III 600 MHz spectrometer, equipped with a 5 mm QCI cryoprobe with a z shielded pulsed-field gradient coil, using 5 mm tubes filled with 500 μL of the sample solution. 1 H NMR spectra were acquired with 64 transients, over a spectral width of 20.55 ppm (offset at 4.7 ppm), at a fixed receiver gain (1), and using 30 s of interpulse delay. 13 C inverse 1 H gated decoupled experiments were performed with 13,312 transients, over a spectral width of 239.0 ppm (offset at 100.0 ppm), using 2.5 s of inter pulses delay.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In recent years, great research efforts have been directed toward replacing fossil-based plastics with more sustainable alternatives from renewable resources to reduce the environmental impact of plastics. Among them, poly­(lactic acid) (PLA), a bio-based aliphatic polyester, is one of the most attractive bioplastics of interest to researchers and industry. The current world production of PLA is around 240,000 tons per year and is expected to double by 2023 . PLA has gained commercial significance, as it combines high mechanical strength, biodegradability, and good melt processability by conventional techniques used for thermoplastics, such as extrusion, injection molding, and thermoforming. , On the other hand, the industrial applications of PLA are narrowed by its relatively high cost, brittleness, slow crystallization rate, and poor barrier properties. , Several biocomposites of PLA with natural fillers have been developed recently to overcome the drawbacks of PLA, while reducing the material cost. , In particular, cellulose, a linear polysaccharide consisting of d -glucose units connected by β-1,4- d -glycosidic bonds, is the most abundant natural biopolymer.…”
Section: Introductionmentioning
confidence: 99%
“…Other disadvantages of using vegetable oils are the increase in flammability and the economic inefficiency, due to the high oil quantity consumption in the impregnation process. The above disadvantages can be overcome by the replacement of oils with polymers based on modified vegetable oils. , These polymers can be modified with antifungal, photo-stabilizing, or fireproof materials and coated on the wood surface to form protective films. Such materials made the subject of few recent studies focused on wood antifungal and thermal protection. , …”
Section: Introductionmentioning
confidence: 99%
“…The above disadvantages can be overcome by the replacement of oils with polymers based on modified vegetable oils. 18,19 These polymers can be modified with antifungal, photo-stabilizing, or fireproof materials and coated on the wood surface to form protective films. Such materials made the subject of few recent studies focused on wood antifungal and thermal protection.…”
Section: Introductionmentioning
confidence: 99%